IMPLEMENTATION OF MULTICULTURAL VALUES IN ISLAMIC RELIGIOUS EDUCATION AT MAS DARUL MURSYID - Siregar, Hendra Irwandi; Ritonga, Aisahrani; Gultom, Yusrina; Chandra, Dewi; Asari, Hasan (Sekolah Tinggi Agama Islam Al Hidayah Bogor, 2025)
This study aims to analyze the implementation of multicultural values in Islamic Religious Education (PAI) at the Private Madrasah Aliyah (MAS) Darul Mursyid. Multiculturalism is an essential concept for fostering tolerance and harmony among religious communities in Indonesia; however, its implementation still requires special attention within the educational context. The research was conducted using a descriptive qualitative method, employing data collection techniques such as observation, in-depth interviews, and document analysis. The research subjects included PAI teachers, the head of the madrasah, and students at MAS Darul Mursyid. The findings indicate that the implementation of multicultural values in the PAI curriculum is carried out through several approaches: (1) the development of an inclusive curriculum, (2) dialogic and interactive teaching methods, (3) emphasis on values of togetherness and mutual respect, and (4) extracurricular activities that support multicultural understanding. The study reveals that PAI teachers have integrated multicultural values into lesson plans (RPP) by employing teaching strategies that promote tolerance, inclusivity, and mutual understanding. Success indicators include an enhanced understanding among students of religious, cultural, and ethnic diversity, as well as the development of mutual respect among members of the school community. The implications of this research highlight the need for the continuous development of PAI teaching models to internalize multicultural values. Recommendations from the study include curriculum refinement, teacher training, and the development of more participatory teaching methods.